Reexamining Salatiga as a Tolerant City in Java: An Exposure of Lesser-Known Facts - M. Ali Sofyan; Alfi Qonita Badi'ati (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2022)
Salatiga has been known as one of the most tolerant cities in Java and Indonesia. Such an achievement refers to the 2021 Tolerant City Index (Indeks Kota Toleran) report released by the SETARA Institute that provides a baseline or assessment of the city government's performance in managing harmony, tolerance, Indonesian national insight, and social inclusion. This article wants to reexamine whether Salatiga is truly a tolerant city and fully implements freedom of religion and belief. The study uses a qualitative approach to interpret interactions between various religious followers in Salatiga. It employs Bielefeldt's analysis and human rights perspectives to reveal the events that actually happened. This study found that the people of Salatiga claim to live in harmony and maintain religious freedom, even though conflicts still occur occasionally. Such conflicts, for example, are seen in disputes about the IAIN Salatiga’ choir team performing at the church and in several social conflicts between Muslims and Christians. Besides, the existence of several religion-based communities, such as Muslim cemeteries, Muslim housing, and Muslim campuses, also justifies the fact of social disharmony in Salatiga because they are not in accordance with the principle of freedom of religion.